STUDY OF IMPULSE BUYING ON LIVE STREAMING: EFFECTS OF HEDONIC SHOPPING MOTIVATION AND SALES PROMOTION - Maulana Wahyu Sasongko; Artanti, Yessy (Jurnal Mebis, 2024)
Shopee Live is a live streaming video feature where sellers can selland interact directly with buyers using the Shopee Live streamingplatform. Several factors come into play. The reason whyconsumers are driven to make unplanned purchases is because ofinternal and external factors. Internal factors are mood and feelingof joy when shopping also known as hedonic shopping motivationand external factors that influence impulse buying which are storeenvironment and promotions. This research aims to analyze anddiscuss the influence of hedonic shopping motivation and salespromotion on impulse buying (study of fashion products onShopee Live Streaming). This research uses a quantitativeapproach. The sample used in this research was non-probabilitysampling with a purposive sampling method. The number ofsamples is 200 people. Research results on hedonic shoppingmotivation and sales promotion partially positively andsignificantly affect impulse buying.